2017
DOI: 10.1039/c7ra03878j
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition and photoluminescence properties of wurtzite CdS:Eu3+ nanoparticles under high pressure

Abstract: Eu dopant increases the phase transition pressure from wurtzite to rocksalt structure compared with CdS nanoparticles. The PL peaks of the Eu3+ ions can used as pressure probe after the quenching of the PL peaks of rocksalt structure CdS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…2a). The re-deposited CdS may enhance the crystallinity of the CdS substrate in the hydrothermal system's high-temperature and high-pressure environment [13,14]. One of the advantages of this recrystallization and redeposition process is that the freshly generated CdS preferentially fills the cavity on the original CdS substrate (Fig.…”
Section: Effect Of Nh 4 F Additive On Cds Recrystallizationmentioning
confidence: 99%
“…2a). The re-deposited CdS may enhance the crystallinity of the CdS substrate in the hydrothermal system's high-temperature and high-pressure environment [13,14]. One of the advantages of this recrystallization and redeposition process is that the freshly generated CdS preferentially fills the cavity on the original CdS substrate (Fig.…”
Section: Effect Of Nh 4 F Additive On Cds Recrystallizationmentioning
confidence: 99%
“…Cadmium sulfide thin film have attract increasing interest, in new year's because of its widely direct band gap energies, electrical properties, optical and stability, different ways, that as chemical vapor deposition, spray pyrolysis and sputtering, and successive ionic coat adsorption and reaction had use for depositing Cadmium sulfide films. The efficiency of Cadmium sulfide semiconductor film is amended by change it's optical and electrical properties by doping with some elements that as copper, Erbium ,and Gallium [7].Organic material carrying function collection had been use as fixed stabilizer for the solution compilation of CdS nanomaterial's with numerous monarchy. For example, polyester constraint with a thiol edge association was used us covalently attach stabilizers for the elaboration of stable Cadmium sulfide nanoclusters in tetrahydrofuran (THF), dimethyl form amide (DMF) and, that was further use for the elaboration for homogeneous scuttle of Cadmium sulfide particles.…”
Section: Introductionmentioning
confidence: 99%
“…5 In another study reported by Changwen Hu et al, Cd 0.5 Zn 0.5 SQDs@C 3 N 4 photocatalyst has been stated to show remarkable hydrogen production performance and high stability under visible light, which were attributed to strong electronic coupling between Cd 0.5 Zn 0.5 S and g-C 3 N 4. 13 Different methods such as thermal annealing, 14 precipitation, 15 and high pressure application 16 have been used to control the crystal structure and obtain hexagonal crystal structure. However, the PC activity, photo-stability, and efficiency of this photocatalyst still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the crystal structure of composite remarkably affects the PC activities of semiconductors. 13 Different methods such as thermal annealing, 14 precipitation, 15 and high pressure application 16 have been used to control the crystal structure and obtain hexagonal crystal structure. Photocatalysts with a cubic crystal structure may have the limits such as low thermal stability, poor visible light adsorption, and low hydrogen production rate.…”
Section: Introductionmentioning
confidence: 99%